Memorias de El Prado : arquitectura y urbanismo 1920-1960 - Ferro Bayona, Jesús, 1943-; Llanos Díaz, Rossana (Universidad del Norte Editorial, 2016)
More than 100 photographs rescued from the historical archives of the Compaänâia Urbanizadora El Prado and from the architectural firm Parrish & Co., accompanied by texts with relevant historical information, integrate this edition about "El Prado" neighborhood, one of the most emblematic areas of Barranquilla b25.00 a170720.